JavaScript Web applications - MacCaw, Alex (O'Reilly, 2011)
"Building rich JavaScript applications that bring a desktop experience to the Web requires moving state from the server to the client side--not a simple task. This hands-on book takes proficient JavaScript developers through all the steps necessary to create state-of-the-art applications, including structure, templating, frameworks, communicating with the server, and many other issues. Throughout the book, you'll work with real-world example applications to help you grasp the concepts involved. Learn how to create JavaScript applications that offer a more responsive and improved experience"--Provided by publisher.